Fast Antioxidation Kinetics of Glutathione Intracellularly Monitored by a Dual‐Wire Nanosensor - Jiao, Yu‐Ting; Kang, Yi‐Ran; Wen, Ming‐Yong; Wu, Hui‐Qian; Zhang, Xin‐Wei; Huang, Wei‐Hua (Angewandte Chemie International Edition, 2023)
The glutathione (GSH) system is one of the most powerful intracellular antioxidant systems for the elimination of reactive oxygen species (ROS) and maintaining cellular redox homeostasis. However, the rapid kinetics information (at the millisecond to the second level) during the dynamic antioxidation process of the GSH system remains unclear. As such, we specifically developed a novel dual‐wire nanosensor (DWNS) that can selectively and synchronously measure the levels of GSH and ROS with high temporal resolution, and applied it to monitor the transient ROS generation as well as the rapid antioxidation process of the GSH system in individual cancer cells. These measurements revealed that the glutathione peroxidase (GPx) in the GSH system is rapidly initiated against ROS burst in a sub‐second time scale, but the elimination process is short‐lived, ending after a few seconds, while some ROS are still present in the cells. This study is expected to open new perspectives for understanding the GSH antioxidant system and studying some redox imbalance‐related physiological. The rapid kinetics between the glutathione (GSH) system and reactive oxygen species (ROS) remain unclear. We developed a dual‐wire nanosensor that can selectively and synchronously measure intracellular GSH and ROS with a high temporal resolution, and applied it to study resveratrol (RSV)‐treated cancer cells. The GSH system is rapidly triggered by the ROS burst in a sub‐second time scale and works only for a few seconds with some residual ROS.